An examination of the martyrdom of Catholicos Zak‘aria II of Ałt‘amar in the Lake Van Region, in the context of Armenia's late medieval (1378-1425) political and ecclesiastical history - Shahinian, A (2022)
This dissertation is a multifaceted investigation of Christian martyrdom in late medieval Armenia (between the years of 1378 – 1425), in the Lake Van region, particularly in the administrative centre of Ostan, historically known as the district of Ṙštunik‘, in the Vaspurakan region. The questions explore the occurrences of martyrdom, the historical accuracy and context of the martyr accounts, and their theological significance and implications. The thesis introduces, for the first time in the English translation, the writings, compilations, and lives of two eminent doctors of the church in the Armenian tradition: Grigor Cerenc‘ Xlat‘ec‘i (1349 – 1425) and Matt‘ēos J̌ułayec‘i (1349 – 1411).